Can credit related macroprudential instruments be effective in reducing the correlation between economic and credit growth? Cross-country evidence - Mehmed Ganić (Journal of Central Banking Theory and Practice, 2023)
The study investigates effectiveness of selected credit related macro prudential instruments in reducing the correlation between economic and credit growth in European emerging countries between 2000 and 2017. Two GMM (Generalized Method of Moments) estimators are used to empirically investigate the validity of tightening policy actions. Although greater attention to MMPs is found in both European regions the study finds some differences as well. On the level of full sample, the findings confirm our expectation about effectiveness of the selected credit related macroprudential instruments in reducing credit growth. More specifically, the European transition countries proved to be more successful in using macroprudential tools in curbing credit growth than European post-transition countries. It is confirmed that all three employed credit related macroprudential instruments play a key role in curbing credit growth in the expansive stage of business cycle in the European transition countries. It means that a lower economic growth leads to lower effects of credit related macroprudential instruments on credit growth. However, empirical evidence from European post-transition countries shows mixed results followed by the lack of robustness of economic results, but with expected theoretical sign. In fact, introduction of CG limits and FC limits reduce the correlation between GDP growth and credit growth only in one step S-GMM estimator, while a variable of caps on debt-toincome ratio (DTI) not.
Keywords: F3; G18; 330; Credit related macroprudential instruments; credit growth; European emergingcountries; GMM estimators